Epic Stone Butch transmasculinity in the work of Willa Cather - Hammer, K. Allison (Transgender Studies Quarterly, 2020)
Through application of the contemporary term transmasculinity and the more historical stone butch, the author questions the critical tendency to perceive American writer Willa Cather only as lesbian while ignoring or undertheorizing a transgender longing at play in her fiction, short stories, and letters. While biographical evidence must not be approached as simply coterminous with literary production, as literature often exceeds or resists such alignments, Cather's letters in particular suggest a strong identification with her male fictional alliances. Analysis of her letters alongside two of her most treasured, and disparaged, novels, One of Ours (1922) and The Professor's House (1925), conveys Cather's wish for an idealized masculinity, both for herself and for Western culture, that would survive two coeval historical processes and events: the closing of the American frontier and the First World War. Through what the author calls a stone butch “armature,” she and her characters retained masculine dignity despite historical foreclosure of Cather's manly ideal, Winston Churchill's Great Man, who was for her the artistic and intellectual casualty of the period. Cather expressed the peculiar nostalgic longing present in stone butch, and in the explosion of new forms of transmasculinity in the present. This suggests that historical transgender styles don't disappear entirely, even as new categories emerge.
Keywords: 1900-1999; 1910-1919; 1920-1929; amériques; approches et analyses; arts; butch; discipline; identités LGBTQIA2+; personnes trans*; périodes historiques; queer; régions géographiques; états-unis; études littéraires

Radclyffe Hall: A life in the writing - Dellamora, Richard (Haney Foundation series, 2011)
The Well of Loneliness is probably the most famous lesbian novel ever written, and certainly the most widely read. It contains no explicit sex scenes, yet in 1928, the year in which the novel was published, it was deemed obscene in a British court of law for its defense of sexual inversion and was forbidden for sale or import into England. Its author, Radclyffe Hall, was already well-known as a writer and West End celebrity, but the fame and notoriety of that one book has all but eclipsed a literary output of some half-dozen other novels and several volumes of poetry. In Radclyffe Hall: A Life in the Writing Richard Dellamora offers the first full look at the entire range of Hall's published and unpublished works of fiction, poetry, and autobiography and reads through them to demonstrate how she continually played with the details of her own life to help fashion her own identity as well as to bring into existence a public lesbian culture. Along the way, Dellamora revises many of the truisms about Hall that had their origins in the memoirs of her long-term partner, Una Troubridge, and that have found an afterlife in the writings of Hall's biographers. In detailing Hall's explorations of the self, Dellamora is the first seriously to consider their contexts in Freudian psychoanalysis as understood in England in the 1920s. As important, he uncovers Hall's involvement with other modes of speculative psychology, including Spiritualism, Theosophy, and an eclectic brand of Christian and Buddhist mysticism. Dellamora's Hall is a woman of complex accommodations, able to reconcile her marriage to Troubridge with her passionate affairs with other women, and her experimental approach to gender and sexuality with her conservative politics and Catholicism. She is, above all, a thinker continually inventive about the connections between selfhood and desire, a figure who has much to contribute to our own efforts to understand transgendered and transsexual existence today.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires